Experimental study on seismic performance of glulam-concrete composite beam-to-column joints. (15th March 2020) - Zhang, Jing; Hu, Xiamin; Sun, Qimeng; Zhang, Yijie; Zhu, Wenwen; Li, Lin
Abstract: Timber-concrete composite (TCC) structure has received extensive attention because of its good structural performance, ease of assembly, low energy consumption, better acoustic performance and fire resistance. However, many studies have concentrated on mechanical performance of TCC beams and shear performance of connectors, and very limited work is reported on the seismic performance of TCC joints. This paper investigates the seismic performance of glulam-concrete composite joints with different connection types. The experimental program involved four full-scale glulam-concrete composite beam-to-column joint specimens subjected to reversed cyclic loading tests. The deformation characteristics, failure modes, hysteretic performance, load-carrying capacity, strain distribution, energy dissipation capacity and stiffness degradation are discussed. Additionally, the influence of different connection types and reinforced concrete slab on composite joints is analyzed by comparing six specimens. Finally, a model was proposed to estimate initial rotation stiffness of glulam-concrete composite beam-to-column joint under hogging moment.